The Impact of Community Contribution on the Academic Achievement of Students - Sivananthan, P.; Wedikandage, L.N.P. (International Journal of Research and Innovation in Social Science, 2023)
A school is a sub-organization of the community, and both are important for developing the other; a school alone cannot achieve success without the cooperation of the community. Hence, the school needs to obtain the cooperation of the community for the growth of the students’ education. The objectives of this study were to measure the present status of the community contribution to improving the academic achievement of students, evaluate actions taken by schools to increase community contribution, analyze the relationship between actions taken by schools and community contribution, and analyze the impact of the community contribution on the academic achievement of students. This study was conducted in a quantitative domain with a descriptive survey design. Questionnaires and documents were used to gather data. Ten principals, ten deputy principals, forty teachers, twenty parents, and twenty past pupils were selected as samples using purposive sampling techniques. A descriptive analysis method was used to analyze the data. The following results have been obtained: the present status of community contribution was at a low level, the actions taken by the school to increase community contribution were high, and the actions taken by schools had a moderately positive impact on community contribution. Also, the community contribution had a moderately positive impact on the academic achievement of students. As a result, there will be a positive impact on the academic achievement of students if the schools have an effective relationship with their community.
Keywords: Community Contribution; Student’s Academic Achievement; School Community Relationship